RANCANGAN BETON NORMAL FC’ 19,3 MPA MENGGUNAKAN AGREGAT HALUS DAERAH GRADASI NO.2 DENGAN CAMPURAN VARIASI AGREGAT KASAR - Umar Khatab; Dina Putrisia Ningsih; Noviarti Noviarti (Ensiklopedia of Journal, 2022)
The quality of an aggregate in a concrete mixture is one of the factors that affect the quality of the concrete. Geographically, Payakumbuh City and District 50 cities are passed by several rivers where the river's products are used by the local community as building material. This research uses a quantitative approach, the research method uses experiment. The results of this study found that the average compressive strength of normal fc concrete was 19.3 Mpa at the age of 14 days using coarse aggregate from Halaban river, the compressive strength value was 21.68 Mpa. The average compressive strength of normal concrete using the coarse aggregate mixture of Halaban and Bukik Limbuku river is 20.98 MPa and the average compressive strength of normal concrete using a mixture of coarse aggregate Halaban and Batang Agam river is 20.35 Mpa. The conclusion of this study is that coarse aggregate from Bukik Limbuku and Batang Agam river, although the quality of the gradation not include in the SNI standart, but after mixing the coarse aggregate from Halaban - Limbuku and Halaban - Batang Agam, the compressive strength more than fc. '19.3 Mpa.Keywords: Material, Concrete Quality, Compressive Strength, Gradation.